1977
DOI: 10.1111/j.1476-5381.1977.tb07530.x
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Bulb Ablation in the Rat: Behavioural Changes and Their Reversal by Antidepressant Drugs

Abstract: I The effects of bilateral olfactory bulbectomy, sham-operation and inducement of peripheral anosmia were studied on locomotor activity, passive avoidance acquisition and irritability. 2 Bulbectomized rats were hyperactive, deficient at learning a step-down passive avoidance response and hyperirritable. Peripheral anosmia, induced by intranasal infusion of ZnSO4 solution resulted in no behavioural changes. 3 Chronic pretreatment with amitriptyline (3 and 10mg/kg) and a tetracyclic antidepressant mianserin (Org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(45 citation statements)
references
References 23 publications
(25 reference statements)
5
40
0
Order By: Relevance
“…10 Increased activity in an open field test is one of the quickest and most consistently reported behavioural changes in the OBX rats, 10,49,56 which does not occur as a consequence of the loss of smell. 42 The lesioning of the serotonergic projections to the olfactory bulb lesion (OB) with a local injection of the neurotoxin 5,7-dihydroxytrypramine (5,7-DHT) also produced hyperactivity in the open field test, which was also the case in OBX rats, 10,24 suggesting effects of the brain serotonergic system on the behavioural changes observed in the OBX rats. The hyperactivity was reversed by chronic administration of amitryiptyline and mianserine.…”
Section: Behavioural Changes In Obx Ratsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Increased activity in an open field test is one of the quickest and most consistently reported behavioural changes in the OBX rats, 10,49,56 which does not occur as a consequence of the loss of smell. 42 The lesioning of the serotonergic projections to the olfactory bulb lesion (OB) with a local injection of the neurotoxin 5,7-dihydroxytrypramine (5,7-DHT) also produced hyperactivity in the open field test, which was also the case in OBX rats, 10,24 suggesting effects of the brain serotonergic system on the behavioural changes observed in the OBX rats. The hyperactivity was reversed by chronic administration of amitryiptyline and mianserine.…”
Section: Behavioural Changes In Obx Ratsmentioning
confidence: 99%
“…10 It was shown, more than three decades ago, that behavioural changes in olfactory bulbectomized (OBX) rats (e.g., hyperactivity, passive avoidance and irritability) were reversed following chronic antidepressant treatment. 42 The relationship…”
Section: Olfactory Bulbectomized Rat As a Model Of Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic deprivation of olfaction, the primary sensory mode in rats, constitutes a stress of high intensity, and the behavioral deficits induced by OB are primarily the result of alterations in neuronal functions, which is supported by the phenomenon that the behavioral deficits can be reversed by antidepressant treatments although the olfactory bulbs are nonexistent (van Riezen et al, 1977;Jesberger and Richardson, 1988;Mar et al, 2000;O'Neil and Moore, 2003). The depression symptom-resembling deficits in OB rats can be normalized by chronic, not acute, antidepressant treatments (Jesberger and Richardson, 1985;Kelly et al, 1997).…”
Section: Discussionmentioning
confidence: 78%
“…The results for the effects of bile duct ligation on sleeping times are shown in Figure 1 and it can be seen that they showed a significant rise in the ligated We have established that antidepressant drugs selectively reverse the effects of bilateral olfactory bulb ablation (van Riezen, Schnieden & Wren, 1977;Cairncross, Cox, Forster & Wren, 1977a) and have recently demonstrated that bilateral intrabulb injection of 5,6-dihydroxytryptamine (5,6-DHT, 8tig) produces similar behavioural and biochemical effects to bulbectomy (Cairncross, Cox, Forster & Wren, 1977b). We have now attempted to assess the susceptibility of the 5,6-DHT-induced syndrome to alteration by psychotropic drugs.…”
mentioning
confidence: 93%